Effects of amoxicillin on gingival biopsies and oral smears: A cross-sectional study - Alkan, Begüm; Köroğlu, Pınar (Wolters Kluwer Medknow Publications, 2021)
Background: Antibiotic use in research volunteers partaking in dental studies varies widely, as inclusion and exclusion criteria used in participant selection lack strict rules. Aim: We aimed to investigate the most appropriate ending time of amoxicillin therapy in healthy subjects before their recruitment and participation in oral histology trials. A cross-sectional design study was conducted in Istanbul, Turkey, between October 2018 and June 2019. Subjects and Methods: Study participants who had undergone a previous course of amoxicillin were divided into three groups according to the amount of time since their last antibiotic dose: group I, within 1 month; group II, within 4-6 months; and group III, within 7-12 months. Periodontal parameters were measured, and smear samples were obtained from buccal mucosa and keratinized gingiva. Gingival biopsies were taken from the upper premolars. Genetic damage and histopathological damage were analyzed with Feulgen reaction and with hematoxylin-eosin staining. Data were analyzed using the Mann-Whitney U, Kruskal-Wallis, and the Pearson Chi-square tests. Results: There were no significant differences in the periodontal parameters and sociodemographic characteristics between the groups (P > 0.05). Higher genetic and histopathological damage scores were observed in group I, which were significantly different compared to the other groups (P < 0.05). No significant differences were observed between groups II and III (P > 0.05). Conclusions: When selecting healthy participants for oral histology trials, at least 3 months should pass after the final dose of amoxicillin is taken to avoid negative effects on gingival tissue and smear samples.
Keywords: Antibacterial Agents; Chromosome-Defective Micronuclei; Cytology; Histopathology; Periodontium